The use of market analytics in the recruitment of high-potentials in the pharmaceutical industry. (3rd June 2019) - Posthumus, Jan; Bozer, Gil; Santora, Joseph C.
This article investigates the use of segmentation and targeting instruments as well as market data in the recruitment of so-called 'high potentials' in the pharmaceutical industry. The grounded theory method (GTM) is used within the framework of contingency theory to explore key contextual factors that influence segmentation and targeting. Fifteen corporate human resource professionals and executive recruiters from pharmaceutical companies based in Europe and the USA were interviewed. The study found that a company's need for certain groups of high potentials (e.g., clinical development professionals), the scarcity of certain highly-sought employee groups, and the capabilities and attitudes of human resource personnel were key determinants of which analytical instruments, such as market analysis, segmentation, and targeting, were implemented. Finally, theoretical and practical implications are provided for HR practitioners concerned with meeting recruitment goals.